Struktur naratif legenda penamaan Perumahan Watu Banteng di Pandaan, Pasuruan - Laili, Rani Nuzulul; Sulistyorini, Dwi (Universitas Mulawarman, 2024)
The naming of an area is often inseparable from the origins and legends associated with the area. This research focuses on the legend behind the naming of Watu Banteng, which is the name of a residential as well as the name of the area. The origin story or legend of Watu Banteng Residential is analyzed based on the theory of narrative structure according to A.J. Greimas. This research uses a descriptive method with a qualitative approach. It aims to describe the actant scheme and functional scheme contained in the legend of the name of Watu Banteng Residential. Data were collected directly through observation, interviews, and documentation conducted on 10 March 2024 in Jalan Sedap Malam, Jogonalan, Jogosari Village, Pandaan District, Pasuruan Regency. The results showed the existence of an actant scheme, which includes sender, object, receiver, subject, helper, and opponent. In addition, there is also a functional scheme that includes the initial situation, transformation (skill test stage, main test stage, and glory stage), and the final situation in the legend of the name of Watu Banteng Residential.